Analisis Gaya Komunikasi Kepemimpinan Kepala Sekolah SMP Negeri 13 Samarinda dalam Meningkatkan Kinerja Pegawai dan Guru - Hasbar, Muhammad Hafidz Alfidhin; Alfando W S, Johantan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The purpose of this study was to determine and analyze the leadership communication style of the Principal of SMP Negeri 13 Samarinda in improving employee performance. The type of research used is descriptive qualitative research. Using data analysis with the Miles and Huberman method, namely data analysis that begins with the process of collecting, reducing, and presenting data and drawing conclusions. Based on the results of the study, the Head of SMP Negeri 13 Samarinda, used the communication methods of Equalitarian style, Structuring style, Dynamic style, and Relinquishing Style. The Equalitarian style is the best communication method to use in an agency because this style establishes two-way communication based on factors related to equality. There is a reciprocal flow of communication that defines this communication style. Users of this type of communication usually have a high sense of concern for employees and are able to establish strong relationships, so the communication tends to be done openly and is felt to be beneficial in fostering empathy and cooperation.